2020
DOI: 10.1177/0361198120918246
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Method to Assess Efficacy of Dust Suppressants for Dirt and Gravel Roads

Abstract: Particulate matter (PM) generated from dirt and gravel roads is a concern for both human and environmental health. To help reduce the amount of PM generated, many states allow the use of water coproduced from oil and gas wells (i.e., brines) as road dust suppressants. However, few methods exist to quantify the effectiveness of these brines and other dust suppressants. Here we designed and tested a bench-scale method to test the efficacy of dust suppressants on dirt and gravel road materials. The Standard Proct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…At the time of publication, Tasker et al (2018) identified 13 U.S. states that utilized conventional O&G wastewater for dust suppression and deicing, targeting high TDS brines enriched in Ca and Mg. , Conventional and unconventional produced waters share similar inorganic chemistry . While HFFF samples were utilized in this study, the developed CrunchFlow code can be applied to both conventional and unconventional produced waters.…”
Section: Resultsmentioning
confidence: 61%
“…At the time of publication, Tasker et al (2018) identified 13 U.S. states that utilized conventional O&G wastewater for dust suppression and deicing, targeting high TDS brines enriched in Ca and Mg. , Conventional and unconventional produced waters share similar inorganic chemistry . While HFFF samples were utilized in this study, the developed CrunchFlow code can be applied to both conventional and unconventional produced waters.…”
Section: Resultsmentioning
confidence: 61%